Perception on the Use of Plastinated Specimen in Anatomy Learning Among Preclinical Medical Students of UNIKL RCMP, Malaysia - ATM Emdadul Haque (Journal of Global Pharma Technology, 2017)
The scarcity of cadaver donation nowadays, consequently, the availability of fresh specimens will be drastically diminished. Plastinated specimens have been introduced as a supplement but are still not widely used in Malaysia.  This study aims to assess the knowledge on plastinated specimens and to determine the perception of preclinical medical students of UniKL RCMP about the use of plastinated specimen in studying anatomy.  A cross-sectional study was done on 143 preclinical medical students of UniKL RCMP using a simple random sampling method. A structured, self-administered questionnaire was used to collect socio-demographic data and information regarding perception on the use of plastinated specimen.  No significant association was found between gender and level of perception (p=0.458) although male students had a slightly better perception level than female students.  Regarding the relationship between gender and perception score, the mean of perception score was found to be higher in male than in female students but the mean difference was found to be statistically not significant (p=0.427).  Study on the association between year of study and the level of perception showed that the number of Year-II students with good perception was higher than that of Year-I students (p=0.006). On testing the relationship between year of study and perception score, the mean of perception score of Year-II students was found to be higher than Year-I students with the mean difference of 2.068 (p=0.002). Since the perception score toward the use of plastinated specimen for learning of anatomy was only an average among the preclinical MBBS students of UniKL RCMP and the Year-II students were having a better perception than the Year-I students, more frequent and longer exposure to the usage of plastinated specimens in learning anatomy should be encouraged. The increasing difficulty of obtaining donated cadavers experienced in many parts of the world propagated the use of plastinated specimens as a supplementary educational tool will open a new era in the teaching and learning of anatomy.KEYWORDS: Perception, Anatomy Learning, Preclinical Medical Students, UNIKL RCMP, Malaysia.